Pengaruh Literasi Keuangan dan Financial Technology Terhadap Inklusi Keuangan (Studi Kasus Pada Masyarakat Kecamatan Negeri Besar Kabupaten Way Kanan) - Farhansyah, Iqbal; Amna, Luke Suciyati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the influence of financial literacy and financial technology on financial inclusion in the community of Negeri Besar District, Way Kanan Regency, with a final sample of 130 samples. The variables analyzed include financial literacy, which includes understanding financial management and financial technology that integrates technology with financial services. The multiple regression analysis method was used to identify the influence of both variables. The results of the study showed that financial literacy and financial technology had a positive and significant effect on financial inclusion. This finding indicates that increasing financial literacy contributes to increasing access and participation in financial services. The use of financial technology can help people access financial services in a more efficient and effective way. Based on these findings, this study suggests increasing financial literacy and adopting financial technology as the main strategy in improving people's welfare. A good understanding of financial literacy can help people manage their finances more wisely, while the application of financial technology makes it easier for people to access financial services.